Physic nut (Jatropha curcas L.) growth and phytomass accumulation rate - Kurihara, Carlos Hissao (2017)
Jatropha plants are known to be a rustic, low-demanding crop for nutrients and water. For that reason, they have been cultivated in restoring degraded areas or as windbreak. Nevertheless, under appropriate soil and climate conditions, this crop may become an alternative for biodiesel production due to high oil content and industrial quality. Studies on the growth and the phytomass accumulation rate of shoots of perennials permit subsidize management practices of culture, such as the definition of the population and the plant arrangement; it also enables the estimation of demand and potential recycling of nutrients, which contributes to establishing the most suitable amount and time for supplying fertilizers in cover. Studies on plant growth and phytomass accumulation have been conducted for a relatively short period of time, sometimes under greenhouse conditions. This trial design was carried out in Cassilândia-MS, for 52 months, with the objective of evaluating Jatropha growth and phytomass accumulation. The experimental design was completely randomized with four replications and 15 treatments, consisting of evaluation times. Jatropha growth, mainly height, stems and crown diameter, is accentuated in the first 12 to 15 months after seedling transplanting. Crown diameter showed a new growth cycle between the 35th and the 52nd month, superior than observed in the initials stages of growth. Stem phytomass accumulation is relatively low until eight months after seedling transplanting, being considerably increased after this period. Intense senescence and leaf abscission is observed in drier and colder periods of the year.